Dissecting Zika virus transmission by Aedes aegypti and Culex quinquefasciatus mosquitoes to a vertebrate host and its coinfection with Mayaro virus - Krokovsky, Larissa; Lins, Carlos Ralph Batista; Guedes, Duschinka Ribeiro Duarte; da Luz Wallau, Gabriel; Ayres, Constância Flávia Junqueira; Paiva, Marcelo Henrique Santos (Frontiers in Microbiology, 2026)
In recent years, the co-circulation of arboviruses including Zika (ZIKV), dengue (DENV), and chikungunya (CHIKV) has been increasingly reported worldwide, contributing to a complex and poorly understood epidemiological scenario. The simultaneous transmission of multiple arboviruses through a single mosquito bite is a documented phenomenon that can influence disease pathogenesis and modify transmission dynamics. This study investigated the dynamics of ZIKV infection in Aedes aegypti (RecLab) and Culex quinquefasciatus (CqSLab), and assessed the potential for ZIKV and Mayaro virus (MAYV) co-infection and co-transmission by Ae. aegypti. Mosquitoes were artificially blood-fed with ZIKV, MAYV, or both, and allowed to feed on immunodeficient mice. Clinical signs were monitored in mice, and infection was assessed using RT-qPCR. Finally, to complete the transmission cycle evaluation study, naive mosquitoes were subsequently fed on infected mice. Among 12 mice exposed to ZIKV-infected Ae. aegypti, all developed symptoms by days 7–8 post-exposure. Notably, mice bitten by co-infected Ae. aegypti displayed symptoms as early as days 2–3 post-exposure. Mosquitoes feeding on these mice showed high ZIKV infection rates, which were further elevated in the context of co-infection. Regarding the 12 mice exposed to Cx. quinquefasciatus, they showed no signs of infection, despite RT-qPCR positivity. These results validate a standardized murine model for arbovirus studies and reveal enhanced ZIKV transmission potential during co-infection with MAYV. The findings offer key insights into arbovirus co-infection dynamics and their potential impact on epidemiology and pathogenesis.